Advances in the use of video-assisted thoracoscopic lobectomy in lung cancer: sleeve bronchoplasty and arterioplasty. (June 2014) - Nakanishi, Ryoichi; Shinohara, Shinji; Yamashita, Toshihiro; Oyama, Tsunehiro; Hanaka, Tetsuya; Kuboi, Satoshi
SUMMARY : This article focuses on the technical strategies for performing sleeve bronchoplasty and pulmonary arterioplasty as advances in the application of video-assisted thoracoscopic surgery (VATS) as lobectomy with bronchovascular reconstruction is a favorable alternative to pneumonectomy in terms of the pulmonary function. When performing VATS sleeve bronchoplasty or arterioplasty, several technical issues should be discussed, including how to reduce the anastomotic tension of the airway, perform bronchial anastomosis, and clamp the pulmonary artery and select the type of vascular clamp. The traction device technique and continuous suture technique are thought to help surgeons perform VATS sleeve bronchoplasty, while cross-clamping of the pulmonary artery using thoracoscopic instruments aids in carrying out VATS arterioplasty.